Analisis performansi kolektor surya pelat datar dengan diameter lubang sirip berbeda sebagai impinging jet - Astawa, Ketut; Ngurah Putu Tenaya, I Gusti (Jurnal Energi Dan Manufaktur, 2022)
Solar collector is a device that is able to absorb and transfer heat from solar energy to the working fluid. Solar collectors in general, use a mass flow rate of air that is parallel to the absorbent plate, the air entering the inlet will pass through the absorbent plate and exit directly through the outlet. To improve the performance of the solar collector, modifications were made, namely by adding perforated fins with various hole diameters. The hollow fin is intended as a place for hot fluid to flow in the collector. The solar collector used in this study is a flat plate solar collector. The workings of the solar collector itself is that solar radiation is absorbed by the absorber plate and then transferred to the fluid flowing in the pipe above the absorber plate. The intended diameter modification is to make the hole diameters vary from a large diameter near the inlet to a small diameter near the outlet and from a small diameter near the inlet to a large diameter near the outlet which is installed in parallel. Variations in the diameter of the fin holes are 90mm, 70mm, 50mm, 30mm and 10mm while the placement of the perforated fins is done alternately, from large to small diameter and vice versa. The performance obtained is for useful energy from large to small diameter of 108.71 W while from small to large fin diameter 62.23 W. For efficiency it is obtained 22.62% for variations from large to small diameter and 12.38% for small to large variations.